3D printable and stretchable PVA‐PAAm dual network hydrogel with conductivities for wearable sensors. Issue 7 (30th November 2022) - Wei, Fanan; Duan, Tuanjie; Yao, Ligang; Yang, Wenguang
Abstract: Conductive hydrogel has broad potential applications in wearable sensors and flexible electronic devices. However, due to the complicated and restrictive mold‐casting process, the manufacture of hydrogel‐based sensors is still facing great challenges. In this paper, we adopt direct inkjet printing (DIW) technology to fabricate three‐dimensional structures of chemically and physically cross‐linked hydrogels by integrating fumed silica as a rheological modifier into crosslinked poly(vinyl alcohol)/poly(acrylamide) (PVA/PAAm) network. Fumed silica not only enables hydrogels with excellent rheological properties, but also provides more hydrogen bond crosslinking sites, further improving mechanical properties. Meanwhile, calcium chloride (CaCl2 ) is supplemented to construct conductive channels in the hydrogel, which powers the hydrogel with good conductivity and strain sensitivity. The sensor assembled from 3D printed hydrogel shows cycle stability and accurate recognition ability in detecting mechanical deformation and various human movements (for example knee bending and frown). This work extends the application of 3D printing hydrogel in the field of wearable devices. Abstract : The rheological properties of PVA/PAAm hydrogel inks have been improved by the introduction of fumed silica, and fumed silica also provides additional hydrogen bonding cross‐linking sites, further improving the mechanical properties. Meanwhile, the hydrogels have good conductivity and strain sensitivity. The sensor assembled from 3D printed hydrogel shows excellent capabilities in detecting various human movements.